2016
DOI: 10.1063/1.4963126
|View full text |Cite
|
Sign up to set email alerts
|

Stress-determined nucleation sites above GaAs-capped arrays of InAs quantum dots

Abstract: We studied the stress field at the surface of GaAs capping layers of variable thicknesses burying InAs quantum dot arrays using the Finite Element method to solve numerically the equations of the elastic field. The aim is to determine the stress-determined favorable sites for dot nucleation. We show that: (i) depending on the cap thickness, dot distances, and array orientation, sudden transitions in the stress-strain fields occur, leading from a vertical alignment of the dots to an anti-aligned correlation. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…We also point out that Liu et al [29] reported, based on a continuum approach similar to the present one, the existence of a growth-parameter window where vertical anti-alignment could take place also in the absence of surface roughness. A similar conclusion was also drawn by Latini et al for III/V systems [30]. While not ruling out the importance of such results under different conditions, here we have shown that for the present system and growth parameters roughness plays, instead, a decisive role.…”
Section: Continuum Growth Simulations and Interpretation Of The Obser...supporting
confidence: 92%
“…We also point out that Liu et al [29] reported, based on a continuum approach similar to the present one, the existence of a growth-parameter window where vertical anti-alignment could take place also in the absence of surface roughness. A similar conclusion was also drawn by Latini et al for III/V systems [30]. While not ruling out the importance of such results under different conditions, here we have shown that for the present system and growth parameters roughness plays, instead, a decisive role.…”
Section: Continuum Growth Simulations and Interpretation Of The Obser...supporting
confidence: 92%